PERSOALAN ORTOGRAFI PENYERAPAN KOSAKATA SANSKERTA DALAM BAHASA INDONESIA - I Made Sudiana (Balai Bahasa Sulawesi Utara, 2011)
Sanskrit has a different writing system with the Indonesian language. Sanskrit uses Devanagari characters, while the Indonesian uses Latin script. Indonesian absorbs much vocabulary from other languages; one of them is from Sanskrit. Differences in sound system and writing system cause problems in absorption. The issue that arises is how to write words that absorbed it. The writing system in the absorption is often problematic when a language does not recognize the sound of the source language. Sanskrit recognizes certain sounds that do not exist in Indonesian. Differences writing system would also cause problems in the orthography. Orthographic problems in Sanskrit vocabulary absorption into the Indonesian language includes writing fricative sounds, retroﬂex, consonant aspire. labiodental /v/ and bilabial /w/, schwa (pepet), and anusuara.